Does motherhood explain lower wages for women in Macedonia?. Issue 1 (1st January 2018) - Petreski, Blagica; Petreski, Marjan
Abstract: The objective of the paper is to estimate the motherhood wage gap and its contribution to the gender wage gap in Macedonia, after considering workers' characteristics and selectivity bias into the labour market for the childbearing-age population. In particular, it aims to disentangle the extent to which the natural role of women to have and raise children affects the gender wage gap. Due to the large female inactivity in Macedonia, we employ a repeated imputation technique, which imputes the wages of those who are unemployed or inactive. Imputed samples are used to decompose the gaps by weighing and by using a re-centred influence function. The Survey of Income and Living Conditions (2010) is used in the analysis. The results suggest that the motherhood wage gap in Macedonia is fully explained by characteristics and, hence, it does not contribute to the potential reducing of the gender wage gap. The selection is also irrelevant, i.e., its consideration does not alter these conclusions.